Learning Media Recommendations and Criteria for the Validity of Junior High School Mathematics Learning Media Books - Sripatmi, Sripatmi; Azmi, Syahrul; Junaidi, Junaidi; Wulandari, Nourma Pramestie; Lu’luilmaknun, Ulfa (Universitas Muhammadiyah Mataram, 2023)
The low quality of education and the achievement of school accreditation, where one of the assessed aspects is the learning process that should be technology-based, demand teachers to develop instructional media.This research aims to develop reference books and obtain mathematical learning media criteria for junior high school. The research method used is Design Research. Research steps are identification and analysis of problems, drafting prototypes, testing prototypes, and improvements. Research is carried out by reviewing the theories, research results, then developing a learning media reference book that will be used as a teacher's guide in developing mathematics learning media for junior high school. The book that has been developed is further validated by three experts in the field of mathematical learning media. validator consists of lecturers and mathematics teachers for junior high school. The conclusion of this study is that interactive learning is the right learning medium in mathematics learning. Some interactive media that affect math learning outcomes are interactive powerpoints, learning videos, and geogebra media. for the development of learning media, a mathematics learning media reference book was developed for junior high school. References have valid criteria on aspects of the material, language, presentation of materials, and infographics.This research aims to develop reference books and establish criteria for mathematical learning media for junior high school. The research method used is Design Research, which involves the following steps: problem identification and analysis, prototype drafting, prototype testing, and improvement. The research is conducted by reviewing theories and research findings, followed by the development of a learning media reference book that will serve as a teacher's guide for creating mathematics learning media for junior high school. The developed book is then validated by three experts in the field of mathematical learning media, including lecturers and mathematics teachers for junior high school. The conclusion of this study is that interactive learning is an effective medium for mathematics education. Some interactive media that have an impact on math learning outcomes include interactive PowerPoints, instructional videos, and Geogebra. To further enhance the development of learning media, a mathematics learning media reference book has been created specifically for junior high school. This reference book meets valid criteria in terms of material aspects, language usage, presentation of content, and infographics.